The Behavior of Gen Z Muslim Consumers in Purchasing Islamic Products: A Study of the Sharia Economic Perspective - Juita, Risa; , M. Zaki (JAWI : Journal of Ahkam Wa Iqtishad, 2025)
This study aims to analyze the purchasing behavior of Muslim Generation Z (Gen Z) consumers toward Islamic products from the perspective of Islamic economics. Gen Z is known as a digital generation that is critical, rational, and value-oriented; therefore, their purchasing decisions for halal products are influenced not only by religious factors but also by social, economic, and technological aspects. This research employs a qualitative method with a literature review approach, examining empirical studies from the past five years (2020–2025) related to halal digital marketing, halal awareness, Islamic lifestyle, and Islamic economic values.The results reveal that digital marketing strategies play a significant role in shaping Gen Z's perception and purchase intention toward halal products through the strengthening of brand equity and electronic word of mouth (e-WOM). Moreover, halal awareness and Islamic lifestyle are proven to be the main drivers of purchasing decisions, as Gen Z perceives halal products as symbols of authenticity, quality, and moral identity. The implementation of the Islamic marketing mix, emphasizing the values of trustworthiness (amanah), excellence (ihsan), and justice (‘adl), contributes to building consumer trust and loyalty. Meanwhile, religiosity acts as a moderating factor that strengthens the influence of product uniqueness and halal awareness on purchasing decisions. Conceptually, the consumption behavior of Muslim Gen Z reflects a transformation toward an Islamic consumer who is critical, digital, and ethical. These findings highlight the importance of digital marketing strategies that are educational, transparent, and grounded in spiritual values to create a balance between profit, ethics, and blessing (barakah) within Islamic economic practices.